Effects of Standardized Ileal Digestible Lysine on Growth Performance and Economic Return of 108 to 178 lb Grow-Finish Pigs - Larissa L. Becker; Emily E. Scholtz; Joel M DeRouchey; Mike D. Tokach; Jason C. Woodworth; Robert D. Goodband; Jordan T. Gebhardt; Jon A. De Jong; Fangzhou Wu; Kiah M. Gourley; Joe P. Ward; Casey R. Neill (Kansas Agricultural Experiment Station Research Reports, 2021)
A total of 2,124 barrows and gilts (PIC 1050 × DNA 600; initially 107.9 ± 1.31 lb) were used in a 32-d study to determine the optimal level of dietary standardized ileal digestibility (SID) Lys for 108 to 178 lb pigs in a commercial setting. Pigs were randomly allotted to 1 of 5 dietary treatments with 24 to 27 pigs per pen and 16 replications pen treatment. A similar number of barrows and gilts were placed in each pen. Diets were fed over 3 phases (108 to 129, 129 to 156, and 156 to 178 lb, respectively). Dietary treatments were corn-soybean meal-based and contained 10% (phase 1 and 2) or 5% (phase 3) DDGS. Diets were formulated to 85, 95, 103, 110, or 120% of the 2016 PIC SID Lys gilt recommendations as follows: phase 1 SID Lys levels of 0.90, 1.01, 1.09, 1.17 and 1.27%; phase 2 levels of 0.79, 0.87, 0.94, 1.03, and 1.10%; and phase 3 levels of 0.71, 0.78, 0.85, 0.92, and 0.99%, respectively. Overall (d 0 to 32), increasing SID Lys increased (linear,P<0.001) ADG, final body weight, Lys intake/d, and Lys intake/kg of gain with an improvement in F/G (quadratic,P= 0.047). Additionally, feed cost per pig, feed cost per lb of gain, total revenue per pig, and income over feed cost (IOFC) increased (linear,P≤ 0.002) as SID Lys increased. Projecting IOFC, broken line linear and quadratic polynomial models estimated the maximum IOFC at 105.8% and 113.7% SID Lys, respectively. In summary, while growth performance increased linearly up to 120% of the 2016 PIC recommended Lys requirement, the optimal IOFC was 106% to 114%.
Keywords: finishing pig; growth; lysine requirement; economics